Membangun Karakter Islami melalui Etika Bermedia Digital di Era Teknologi Modern Global - Muhammad Reply; Haifa Unnijaah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
The rapid development of digital technology has significantly transformed patterns of communication and social interaction in modern society. Social media has evolved beyond a communication platform and become an important medium for education, information dissemination, and character development. From an Islamic perspective, social media can be utilized as a strategic tool to promote moral values, strengthen ethical awareness, and foster Islamic character based on the teachings of the Qur’an and Hadith. This study aims to analyze the role of social media in building Islamic character and to identify effective and responsible strategies for its utilization in the digital era. This research employs a literature review method with a descriptive-qualitative approach by examining relevant scientific journals, books, and previous studies. The findings indicate that social media contributes positively to the development of Islamic character through digital da’wah, the dissemination of religious knowledge, the enhancement of religious literacy, and the promotion of social awareness and empathy. However, uncontrolled use of social media may also lead to negative consequences, such as the spread of misinformation, cyberbullying, hate speech, and the decline of communication ethics. Therefore, strengthening digital literacy, implementing the principle of tabayyun (information verification), and internalizing Islamic ethical values are essential to ensure that social media is used wisely, productively, and responsibly in shaping a generation with strong moral character in the digital age.